ANALYSIS OF COMPETITIVENESS AND GOVERNMENT POLICIES ON INDONESIAN WHITE JASMINE (Jasminum sambac) FARMING - Liska Simamora; Damara Dinda Nirmalasari Zebua; Yoga Aji Handoko; Suprihati Suprihati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Floriculture is a sub-sector of horticulture that has great potential as a business. One type of floriculture is white jasmine (Jasminum sambac) known as the flower of the nation (Puspa Bangsa). This plant is widely used by the Indonesian society for both traditional and religious ceremonies. In addition, it is also a commodity that potentially increases the volume of national exports. The central production of white jasmine flowers is Central Java Province, specifically in Depok Village, Kandeman District, Batang Regency. The planting area of jasmine flowers in Batang Regency has decreased. This is caused by the lack of young people to continue white jasmine farming, the land conversion of white jasmine flower to rice, or rented out to other utilities. These conditions indicate that white jasmine flower activity is no longer a top priority for farmers in Depok Village. Therefore, this study aims to analyze the competitiveness of white jasmine flowers. This is quantitative research. The sampling was determined by applying purposive sampling with those 30 farmers who are members of the Barokah Farmers Group Association. Data was collected through interviews using a questionnaire. Furthermore, the data were analyzed using the Policy Analysis Matrix. The results showed that white jasmine farming has both competitive advantage (PCR<1) and comparative advantage (DCR<1). The government has protected production inputs (NPCI<1), but has not protected output (NPCO<1).